Ca2+ Dependence of Volume-Regulated VRAC/LRRC8 and TMEM16A Cl– Channels - Centeio, Raquel; Ousingsawat, Jiraporn; Schreiber, Rainer; Kunzelmann, Karl (Frontiers in Cell and Developmental Biology, 2020)
All vertebrate cells activate Cl- currents (ICl,swell) when swollen by hypotonic bath solution. The volume regulated anion channel VRAC has now been identified as LRRC8/SWELL1. However, apart from VRAC, the Ca2+-activated Cl- channel (CaCC) TMEM16A and the phospholipid scramblase and ion channel TMEM16F were suggested to contribute to cell swelling-activated whole cell currents. Cell swelling was shown to induce Ca2+ release from the endoplasmic reticulum and to cause subsequent Ca2+ influx. It is suggested that TMEM16A/F support intracellular Ca2+ signaling and thus Ca2+ dependent activation of VRAC. In the present study we tried to clarify the contribution of TMEM16A to ICl,swell. In HEK293 cells coexpressing LRRC8A and LRRC8C, we found that activation of ICl,swell by hypotonic bath solution (Hypo; 200 mosm/l) was Ca2+ dependent. TMEM16A augmented activation of LRRC8A/C by enhancing swelling-induced local intracellular Ca2+ concentrations. In HT29 cells, knockdown of endogenous TMEM16A attenuated ICl,swell and changed time-independent swelling-activated currents to VRAC-typical time-dependent currents. Activation of ICl,swell by Hypo was attenuated by blocking receptors for inositol trisphosphate and ryanodine (IP3R; RyR), as well as by inhibiting Ca2+ influx. The data suggest that TMEM16A contributes directly to ICl,swell as it is activated through swelling-induced Ca2+ increase. As activation of VRAC is shown to be Ca2+-dependent, TMEM16A augments VRAC currents by facilitating Hypo-induced Ca2+ increase in submembraneous signaling compartments by means of ER tethering.